Immunoadsorption in nephrology and kidney transplantation - Schwenger, Vedat; Morath, Christian (Nephrology, dialysis, transplantation, 2010)
Immunoadsorption finds incremental implementation in the treatment of several autoimmune disorders as well as for kidney transplant indications (see Table 1). As opposed to plasmapheresis, immunoadsorption allows not only a more specific but also a more effective clearance of circulating immunoglobulins without the side effects associated with the substitution of fresh frozen plasma or albumin. In addition, even multiple plasma volumes may be processed, and a reduction of immunoglobulins of 80% and more is feasible [1]. However, one has to consider that plasmapheresis is not only utilized for removal of immunoglobulins but also for the substitution of different plasma components such as ADAMTS-13 in the case of thrombotic thrombocytopenic purpura [2]. Therefore, plasma infusion itself may have beneficial effects independent of the removal of circulating pathogenic substances. The use of plasmapheresis for the treatment of different kidney diseases remains controversial due to a lack of randomized controlled trials demonstrating the benefit of this procedure. This applies even more to immunoadsorption. However, for some indications especially in the field of kidney transplantation, there is now growing evidence pointing to the large potential of this treatment modality. This editorial comment will focus on the available evidence on immunoadsorption in kidney diseases and kidney transplant indications.
Gesehen am 11.07.2023